Cover crop and nitrogen effects on maize productivity in no-tillage systems of the Brazilian cerrados - Maltas, A; Corbeels, Marc; Scopel, E.; Wery, Jacques; Silva, F.A.M. da (Wiley, 2009)
Cover crops in direct seeding mulch‐based cropping (DMC) systems can be an effective tool to optimize N management for crop production in the Brazilian cerrados. The objective of this study was to determine the effect of four cover crops on maize (Zea mays L.) grain yields in two fields that had been under DMC for 3 and 14 yr. We hypothesized that cover crops would optimize N supply to the maize crop, thereby leading to increased yields. Cover crop treatments were: bare fallow (BF), pigeon pea (PP) [Cajanus cajan (L.) Huth], pearl millet [Pennisetum glaucum (L.) R. Br.]–Congo signal grass (PM‐CS) (Brachiaria ruziziensis Germain & Evrard), pigeon pea–finger millet (PP‐FM) [Eleusine coracana (L.) Gaertn.], and sorghum (S) [Sorghum bicolor (L.) Moench]. Experiments were conducted during the 2003–2004 and 2004–2005 growing seasons. In 2003–2004 on the DMC‐14 field, cover crops increased N uptake of zero‐N fertilized maize with 25 to 66 kg N ha−1 compared to BF, which resulted in an increase in grain yield of 0.4 to 2.4 Mg ha−1. Effects on fertilized maize were much less. The highest yield benefits were obtained with pigeon pea and sorghum as sole cover crop. No significant cover crop effects were recorded in 2004–2005. Nitrogen losses under maize estimated on the basis of a simple soil mineral nitrogen balance ranged from 40 to 90 kg N ha−1 in 2003–2004, while they were smaller in 2004–2005 (10–25 kg N ha−1), presumably due to the lower rainfall. Cover crops can have an immediate positive effect on maize productivity under DMC in the cerrados, provided that they are sown immediately after harvest of the main crop.